Organização dos serviços e das comissões de infecção hospitalar e utilização de taxas para o controle de infecção hospitalar em região central do Brasil - D'Alfonso Júnior, Geovanne (2015)
Hospital-acquired infection (HAI) rates are measures which should be obtained only to guide infection control practices. However, it is not clear how well they have been actually used by hospital-acquired infection control committees (HAICCs) to achieve this purpose. This study aimed at assessing the characteristics of Hospital-acquired infection control services (HAICS) and HAICC, HAI rates obtained and, especially, their use in the HAI control process in hospitals from a central region of Brazil. Data were prospected using interviews with 44 healthcare professionals working in the HAI control service of 19 hospitals of the region. It was carried out by one of the researchers, who used as instrument a semi-structured questionnaire. Based on data provided by interviewee professionals, HAICSs and HAICCs are relatively well-structured. The major infection rates established relate to surgical site infections (SSI), pulmonary infection related to mechanical ventilation (MV), urinary tract infection (UTI) related to vesical catheter (VC) and primary bloodstream infection (BSI). During activities carried out, data collection, construction of rates and their dissemination took most of the professionals work time. Forty (90.91%) professionals considered that the rates have been useful in controlling HAI and 34 (77.27%) could remember some measure taken by HAICS fundamentally based on obtained rates. However, it is noticeable that mentioned measures were not, necessarily, triggered and sustained by knowledge of the rates. It has been concluded that HAICSs and HAICCs of the study region have a better infrastructure than the known average in Brazil; activities of data collection and rate construction and dissemination are usually carried out as they have been suggested, but time spent on these activities is not clearly justified by the measures they determine.